1999
DOI: 10.1179/003258999665701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen on supersolidus sintering of modified M35M high speed steel

Abstract: . The diminution of the optimum sintering temperature and the widening of the Water atomised high vanadium M35M high speed sintering gate were proved. It was also demonstrated steel powders with different carbon contents were cold that sintering to full density of modified high carbon-high compacted at 700 MPa and sintered under an N 2 rich vanadium T42, T15, and M35M HSSs under 1150°C is atmosphere. Full density specimens were obtained at possible.10-12 This marks a historical milestone because temperatures b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…In recent years, several articles have been published on the liquid-phase sintering of prealloyed tool steels by means of so-called supersolidus liquid-phase sintering (SLPS). [3][4][5][6][7] Compared to PM-HIP, which requires encapsulation of the powder, the benefits of sintering by SLPS are reduced costs, a greater flexibility with respect to the geometry, and the possibility of producing near-net-shape parts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several articles have been published on the liquid-phase sintering of prealloyed tool steels by means of so-called supersolidus liquid-phase sintering (SLPS). [3][4][5][6][7] Compared to PM-HIP, which requires encapsulation of the powder, the benefits of sintering by SLPS are reduced costs, a greater flexibility with respect to the geometry, and the possibility of producing near-net-shape parts.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in [5,[9][10][11], nitrogen is beneficial to sintering, not only because it can provide sufficient protection against oxidation, but it can also permeate into the matrix of the material and transform the MC carbides found in vacuum sintering into metallic carbonitrides (MX) which are more stable and are able to inhibit grain growth. Nitrogen may also be related to the expansion of the critical liquid +austenite+carbides region as mentioned by Aguirre et al [12].…”
Section: Introductionmentioning
confidence: 93%
“…The application of the PIM process to HSS has been developed in recent years [11][12][13][14][15][16][17][18] and for the production of components of complex shape it is considered better than other manufacturing techniques, such as pressure die compaction, which are limited to the manufacture of parts with simple shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors [18][19][20][21][22][23] include hardness, wear resistance, strength, ductility, and have observed that besides adjusting the composition, this dimensional precision. In addition, a high final sintered denaddition enhances the sintering kinetics and leads to higher sity is important because most properties improve with it.…”
Section: Introductionmentioning
confidence: 99%